Two-factor authentication methods threats analysis - Evseev, S. P.; Tomashevskyy, B. P. (Запорізький національний технічний університет, 2015)
The article considers basic methods of two-factor authentication system constructing on the basis of the use of cryptographic mechanisms to ensure the reliability, of formed authenticators, the risk of various methods of online attacks against a variety of two-factor authentication systems is estimated, as well as a system PassWindow is considered, which provides two-factor authentication on the unique ability of the matrix to transmit information in such a way that it is deciphered only to the imposition of the physical signs of the intended recipient pattern and barcode pattern obtained by digital network devices, resistance to the analysis is provided by a unique barcode card pattern generation as unique statistical images, a sequence of characters, or as more extended in an animated version. The object of the research is the process of improving the integrity and authenticity of data packets in banking transactions security protocols on the basis of two-factor authentication methods. The subject of the study is methods and algorithms of integrity control and authenticity of data packets in banking transaction security protocols on the basis of two-factor authentication methods. The aim of the paper is to increase the integrity and authenticity of data packets in banking transactions security protocols, a banking transaction, threat assessment on two-factor authentication methods. A comparative analysis of various systems with two-factor authentication PassWindow system in opposition to various Internet attack scenario is being carried out. An effective method for monitoring a practical twofactor authentication PassWindow system in its application to the banking system.

У статті розглядаються основні методи побудови системи двофакторної аутентифікації на основі використання криптографічних механізмів забезпечення криптостійкості, аутентифікаторів, які формуються, оцінюється ризик різних методів онлайн-атак проти різних систем двофакторної аутентифікації, а також розглядається система PassWindow, що забезпечує двофакторну аутентифікацію на унікальній здатності частини матриць передавати інформацію таким чином, що вона розшифровується тільки при накладенні фізичного шаблону знаків передбачуваного одержувача і шаблону штрих-коду, одержуваних через електронно-мережеві пристрої користувачів, стійкість до аналізу забезпечується унікальністю формування шаблону штрих-коду картки у вигляді унікальних статистичних зображень, послідовності символів або у вигляді більш розширено анімаційної версії. Об’єктом дослідження є процес підвищення цілісності та автентичності пакетів даних у протоколах безпеки банківських транзакцій на основі методів двофакторної аутентифікації. Предметом дослідження є методи та алгоритми контролю цілісності та автентичності пакетів даних у протоколах безпеки банківських транзакцій на основі методів двофакторної аутентифікації. Метою роботи є підвищення цілісності та автентичності пакетів даних у протоколах безпеки банківських транзакцій, оцінка загроз на методи двофакторної аутентифікації. Проводиться порівняльний аналіз різних систем двофакторної аутентифікації з системою PassWindow у сфері протистояння різним інтернет-сценаріями атак. Пропонується ефективний практичний метод моніторингу системи двофакторної аутентифікації PassWindow при її застосуванні в банківських системах.
Дослідження загроз методів двофакторної аутентифікації
Keywords: two-factor authentication; online attacks; social engineering; двофакторна аутентифікація; онлайн-атаки; соціальна інженерія